(untitled) (Cambridge, UK,New York, 2002)
Prevention, diagnosis and treatment are the watchwords in stroke research, for basic neuroscientists and clinicians alike. This book, from the 22nd Princeton Conference on Cerebrovascular Disease, contains contributions from outstanding investigators on current topics in stroke research. The contents cover the current status and future directions of stroke pathophysiology, diagnosis and treatment, with special emphasis on the molecular and cellular mechanisms of ischaemic cell death and repair, and clinical issues including imaging, risk factors and therapeutic strategies in stroke. Available in both print and online formats, this survey of the basic and clinical science of stroke is an essential resource for all involved in advancing knowledge of cerebrovascular disease.
Keywords: Cerebrovascular disease,Cerebrovascular disease,Cell Death,Bệnh mạch não,Bệnh mạch não; Pathophysiology,Treatment,Sinh lý bệnh học,Sự điều trị